Power Relationships in Vote-Buying in Political Career Progression: A Rational Choice Theory Perspective - Septi Wulandari; Esa Septian; Suprapti Suprapti; Nur Baity Al Wafiroh (Institut Pemerintahan Dalam Negeri, 2024)
The term